Value Creation in Fisheries Supply Chain as A Role Model for Fish Protein Hydrolyzate Cluster Development - Santoso, Sugeng; Soehari, Tjiptogoro Dinarjo; Aprianto, Yoce; Andrean, Dicky; Henny, Henny (Jurnal Rekayasa Mesin, 2020)
To increase the level of competitiveness in the maritime and fisheries industry in Indonesia, the creation of added value products, such as Fish Protein Hydrolyzate (FHP) would be essential to accelerate this mission. This value creation occurs along the fisheries supply chain, including fishermen, shippers, fish processing units, and industry. To assess the innovation maturity, the FHP machine was assessed with the Technology Readiness Level (TRL) and Innovation Readiness Level (IRL). The TLR was carried out by TRL-Meter and IRL was carried out by IRL-Meter. The data was collected by interviews and questionnaires with related stakeholders. The data assessed that the machine met the requirement for TRL level 9 and IRL Level 3. The recommendation for TRL 9 and IRL 3 has been conducted through a strategic partnership with a related state-owned enterprise. Because the FHP shows product competitiveness, gives value-added, and generates value creation in the fisheries supply chain, it could be a role model for the development of the FHP cluster in another location. However, the involvement of local and central governments still needs to be improved significantly. Furthermore, the government should build a conducive ecosystem for technology-based innovation in the country.